LOST Highway: A Multiple-Lane Ant-Trail Algorithm to Reduce Congestion in Large-Population Multi-robot Systems - Abdelaal, Alaa Eldin; Sakr, Maram; Vaughan, Richard (CRV 2017 : proceedings 2017 14th Conference on Computer and Robot Vision : Edmonton, Alberta, Canada, 17-19 May 2017, 2017)
We propose a modification of a well-known ant-inspired trail-following algorithm to reduce congestion in multi-robot systems. Our method results in robots moving in multiple lanes towards their goal location. Our algorithm is inspired by the idea of building multiple-lane highways to mitigate traffic congestion in traffic engineering. We consider the resource transportation task where autonomous robots repeatedly transport goods between a food source and a nest in an initially unknown environment. To evaluate our algorithm, we perform simulation experiments in several environments with and without obstacles. Compared with the baseline SO-LOST algorithm, we find that our modified method increases the system throughput by up to 3.9 times by supporting a larger productive robot population.